The Everyday Making of EU Foreign and Security Policy - Bremberg, Niklas (Edward Elgar Publishing, 2022)
This is an open access title available under the terms of a [CC BY-NC-ND 4.0] License. It is free to read, download and share on Elgaronline.com. This cutting-edge book explores the practices and socialization of the everyday foreign policy making in the European Union (EU), focusing on the individuals who shape and implement the Common Foreign and Security Policy despite a growing dissension among member states.